Effects of Economic Recession on Elderly Patients' Perceptions of Access to Health Care and Medicines in Portugal - FA Costa; I Teixeira; F Duarte-Ramos; L Proença; AR Pedro; C Furtado; JA Silva; J Cabrita (Formifarma, LDA., 2019)
Background In view of the current ﬁnancial and demographic situation in Portugal, accessibility to health care may be affected, including the ability to adhere to medication. Objective To evaluate the perceived effects of the crisis on elderly patient's access to medicines and medical care, and its implications on medicine-taking behaviour. Setting Community pharmacy. Method: A cross-sectional study was undertaken during April 2013, where elderly patients answered a self-administered questionnaire based on their health-related experiences in the current and previous year. Binary logistic regression was used to ascertain the effects of potential predictors on the likelihood of adherence. Main outcome measures self-reported adherence. Results A total of 1231 questionnaires were collected. 27.3% of patients had stopped using treatments or health services in the previous year for ﬁnancial motives; mostly private medical appointments, followed by dentist appointments. Almost 30% of patients stopped purchasing prescribed medicines. Over 20% of patients reduced their use of public services. Out-of-pocket expenses with medicines were considered higher in the current year by 40.1% of patients. The most common strategy developed to cope with increasing costs of medicines was generic substitution, but around 15% of patients also stopped taking their medication or started saving by increasing the interdose interval. Conclusion Reports of decreasing costs with medicines was associated with a decreased likelihood of adherence (OR 0.42; 95% CI 0.27-0.65). Lower perceived health status and having 3 or more co-morbidities were associated with lower odds of adhering, whilst less frequent medical appointments was associated with a higher likelihood of exhibiting adherence. Published in: Int J Clin Pharm. 2017;39:104-12.